2014
DOI: 10.1021/bi4013947
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ligand Mobility Explains Internal Hydration and Reconciles Active Rhodopsin Structures

Abstract: Rhodopsin, the mammalian dim-light receptor, is one of the best-characterized G-protein-coupled receptors, a pharmaceutically important class of membrane proteins that has garnered a great deal of attention because of the recent availability of structural information. Yet the mechanism of rhodopsin activation is not fully understood. Here, we use microsecond-scale all-atom molecular dynamics simulations, validated by solid-state 2H nuclear magnetic resonance spectroscopy, to understand the transition between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
64
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 64 publications
16
64
0
4
Order By: Relevance
“…By starting from the crystal structure and observing a stable 180 rotation about the long axis of the polyene chain, our simulations provide a plausible explanation for these differences. Furthermore, our results provide compelling support for our proposal that the increased ligand flexibility observed in Meta-I could lead to multiple retinal conformations in the active state (12).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…By starting from the crystal structure and observing a stable 180 rotation about the long axis of the polyene chain, our simulations provide a plausible explanation for these differences. Furthermore, our results provide compelling support for our proposal that the increased ligand flexibility observed in Meta-I could lead to multiple retinal conformations in the active state (12).…”
supporting
confidence: 82%
“…It has been shown that the 6-s-trans conformation raises the pK a of the SB, favoring the protonated state (13), as in Meta-I. Moreover, the pathway that occurs from cis to trans is very similar to the one observed in previous longtimescale MD studies that examined the dark / Meta-I transition (11,12).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, in vitro studies of integral membrane proteins or peptides often require that they be reconstituted with membrane lipids (19,(28)(29)(30), where bilayer structural dimensions involving hydrophobic matching and area per lipid are significant factors (1,14,31). The constraints imposed by the area per lipid at the membrane aqueous interface (31) also play an important part in validating molecular dynamics (MD) simulations of lipid bilayers (32) and biomembranes (13,33,34). In such cases, it is essential that investigators have a solid understanding of the membrane bilayer structure itself (35).…”
Section: Introductionmentioning
confidence: 99%